Analisis Isi Kebijakan Peraturan Daerah Kabupaten Kudus Nomor 4 Tahun 2017 Tentang Pengelolaan Sampah - Zumar Syafiq, Ahmad (Fakultas Hukum Universitas Jambi, 2024)
One of the regional regulations that emerged as a form of implementation of the mandate of Law Number 18 of 2008 is Regional Regulation Number 4 of 2017 concerning Waste Management issued by the Kudus Regency Government. This article aims to examine and assess the content of waste management policies in Kudus Regency. This is important to do considering that the success of a policy can be seen, one of the ways, from the contents of the policy. This article only focuses on the content of policy using Merilee S. Grindle's model, which consists of six aspects, namely: interests affected, type of benefits, extent of change envisions, site of decision making, program implementor, and resources committed. Types of normative juridical research with a statutory approach and a conceptual approach. The primary data source is the policy of Kudus Regency Regional Regulation Number 4 of 2017 concerning Waste Management, while the secondary data is in the form of journals related to waste management. The results of the analysis show that: the formation of regional regulations takes into account the physical, biological, social environment and juridical reasons (interest affected); the benefits of regional regulations are making the environment cleaner and healthier, as well as making people aware of the surrounding environment, more disciplined and more empowered in managing waste (type of benefits); the expected changes are improving environmental quality, improving public health, and changing people's mindset and behavior towards waste (extent of change envisions); the decision-making position is the Regional People's Representative Council (DPRD) of Kudus Regency with the joint approval of the Kudus Regent (site of decision making); implementing the policy, namely the Public Works Department (DPU) (program implementor); Policy resources consist of five components, namely man, materials, methods, machines, and money (committed resources).